High performance reinforced concrete, corrosion – resistant into aggressive industrial environments - Vázquez Rodríguez, Francisco Javier; De los Santos, Ulises; Mendoza Rangel, José Manuel; Gómez Rodríguez, Cristian; Arato Tovar, Ana María; Rodríguez Castellanos, Edén Amaral (Bucureşti: Fundaţia "Şerban Solacolu, 2017)
Reinforced concrete structures exposed to aggressive industrial environments suffer different accelerated deterioration mechanisms. In chlor-alkali production plants, the industrial environment contains high concentrations of carbonates and chlorides, damaging the structures and causing constant stoppages and repair processes on the structure of reinforced concrete. In this study, the effect of using internal curing on high performance concrete with low water/binder ratios was studied, implementing pumicite as internal curing agent, chemical additives and replacing Portland cement with pulverized fly ash. Durability measurements conducted were permeability of chloride ions, and carbonation depth under industrial andlaboratory conditions. Results showed that there is a reduction of the aggressive agents transport mechanisms when internal curing is applied. However, measurements at long ages must be done to evaluate the synergistic effect of the agents contained in the industrial environment on the metal reinforcement.